Transmembrane proteins in grape immunity: current knowledge and methodological advances - Gallucci, Alessia; Giordano, Deborah; Facchiano, Angelo; Villano, Clizia; Carputo, Domenico; Aversano, Riccardo (Frontiers in Plant Science, 2024)
Transmembrane proteins (TMPs) are pivotal components of plant defence mechanisms, serving as essential mediators in the response to biotic stresses. These proteins are among the most complex and diverse within plant cells, making their study challenging. In spite of this, relatively few studies have focused on the investigation and characterization of TMPs in plants. This is particularly true for grapevine. This review aims to provide a comprehensive overview of TMP-encoding genes involved in grapevine immunity. These genes include Lysin Motif Receptor-Like Kinases (LysM-RLKs), which are involved in the recognition of pathogens at the apoplastic level, Plant Respiratory Burst Oxidase Homologs (Rbohs), which generate reactive oxygen species (ROS) for host defense, and Sugars Will Eventually be Exported Transporters (SWEETs), which play a role in nutrient allocation and stress responses. Furthermore, the review discusses the methodologies employed to study TMPs, including in vivo, in vitro and in silico approaches, highlighting their strengths and limitations. In vivo studies include the assessment of TMP function in whole plants or plant tissues, while in vitro experiments focus on isolating and characterizing either specific TMPs or their components. In silico analyses utilize computational tools to predict protein structure, function, and interactions. By identifying and characterizing genes encoding TMPs involved in grapevine immunity, researchers can develop strategies to enhance grapevine resilience and lead to more sustainable viticulture.